Muscle atrophy in chronic inflammatory demyelinating polyneuropathy: a computed tomography assessment. (29th March 2014) - Ohyama, K.; Koike, H.; Katsuno, M.; Takahashi, M.; Hashimoto, R.; Kawagashira, Y.; Iijima, M.; Adachi, H.; Watanabe, H.; Sobue, G.
<x xml:space="preserve">Abstract</x> Background and purpose Muscle atrophy is generally mild in patients with chronic inflammatory demyelinating polyneuropathy (CIDP) compared with the severity and duration of the muscle weakness. Muscle atrophy was evaluated using computed tomography (CT) in patients with CIDP. Methods Thirty‐one patients with typical CIDP who satisfied the diagnostic criteria for the definite CIDP classification proposed by the European Federation of Neurological Societies and the Peripheral Nerve Society were assessed. The clinicopathological findings in patients with muscle atrophy were also compared with those in patients without atrophy. Results Computed tomography evidence was found of marked muscle atrophy with findings suggestive of fatty degeneration in 11 of the 31 patients with CIDP. CT‐assessed muscle atrophy was in the lower extremities, particularly in the ankle plantarflexor muscles. Muscle weakness, which reflects the presence of muscle atrophy, tended to be more pronounced in the lower extremities than in the upper extremities in patients with muscle atrophy, whereas the upper and lower limbs tended to be equally affected in patients without muscle atrophy. Nerve conduction examinations revealed significantly greater reductions in compound muscle action potential amplitudes in the tibial nerves of patients with muscle atrophy. Sural nerve biopsy findings were similar in both groups. The functional prognoses after immunomodulatory therapies were significantly poorer amongst patients with muscle atrophy. Conclusions Muscle atrophy was present in a subgroup of patients with CIDP, including patients with a typical form of the disease. These patients tended to demonstrate predominant motor impairments of the lower extremities and poorer functional prognoses.